2019
DOI: 10.1159/000504790
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Ureterorenoscopy Outcomes in Proximal Ureteral Stones: A Multicenter Study of Aegean Study Group of the Society of Urological Surgery

Abstract: <b><i>Introduction:</i></b> We aimed to evaluate the predictive factors in a holistic manner for ureterorenoscopy (URS) outcomes in proximal ureteral stones by a multicenter study. <b><i>Materials and Methods:</i></b> The data of patients who underwent URS for proximal ureteral stones between the years 2015 and 2018 in eight centers were recorded retrospectively. Patients were divided into two groups according to URS success: Group 1 consisted of patients with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Turunc et al 16 studied the factors that affect the success of rURS for ureteral stones in pediatric patients, and they demonstrated a significant reverse correlation between stone size and SFR (p = 0.007). In a multicenter study, Sen et al 17 retrospectively evaluated, in a holistic manner, the predictive factors from URS involving upper ureteral stones. They found that stone area is one of the key risk factors affecting URS success (OR = 0.993, p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Turunc et al 16 studied the factors that affect the success of rURS for ureteral stones in pediatric patients, and they demonstrated a significant reverse correlation between stone size and SFR (p = 0.007). In a multicenter study, Sen et al 17 retrospectively evaluated, in a holistic manner, the predictive factors from URS involving upper ureteral stones. They found that stone area is one of the key risk factors affecting URS success (OR = 0.993, p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Sen, Sancak, Günlüsoy and Bangash reported that stone size is associated with the success rate of semi-rigid ureteroscopy in proximal ureteral stone. 2,6,10,12 There are studies that claim the opposite. [13][14][15] In this study, the size of stones were similar in both the groups (p=0.903).…”
Section: 12mentioning
confidence: 99%
“…Urologists consider many factors, such as location of stone, stone size, patient's age, degree of hydro nephrosis, symptom severity, accompanying bacterial infection, status of solitary kidney, patient expectations and technical equipment, when making treatment decisions. 2 Stones smaller than 5 mm are more suitable for spontaneous passage through the ureter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported different probabilities: up to 47% (36-48%) with a stone size of 5-10 mm and 68% (46-85%) with a stone size of <5 mm [7]. Ultimately, it is important for clinicians to discuss these options with the patient and for them to decide together whether to carry out an endoscopic procedure or wait for spontaneous stone passage with regular follow-up [8,9]. Thus, an exact measurement of stone size is very important to help facilitate these discussions with the patient.…”
Section: Introductionmentioning
confidence: 99%